Combined effects of exercise training and high doses of anabolic steroids on cardiac autonomic modulation and ventricular repolarization properties in rats - Marocolo, Moacir; Katayama, Pedro L. [UNESP]; Meireles, Anderson; Barbosa Neto, Octavio (Canadian Science Publishing, 2019)
Several studies have reported that high doses of synthetic anabolic androgenic steroids (AAS) can have serious negative effects on health, including the cardiovascular system. The aim of this study was to evaluate the combined effects of AAS and exercise training on ventricular repolarization and cardiac autonomic modulation in rats. Male Wistar rats were allocated into 4 groups: sedentary rats treated with vehicle, sedentary rats treated with nandrolone decanoate, swimming-trained rats treated with vehicle, and swimming-trained rats treated with nandrolone decanoate. Ventricular repolarization was evaluated by electrocardiographic analysis of QT interval and QT dispersion. Cardiac autonomic modulation was assessed by heart rate variability. Our results show that AAS increased QT interval and QT dispersion in sedentary rats treated with nandrolone decanoate as compared to sedentary rats treated with vehicle, indicating AAS-induced ventricular repolarization abnormalities. When rats treated with nandrolone decanoate were subjected to concomitant exercise training, ventricular repolarization was normalized. On the other hand, AAS-induced reduction in cardiac parasympathetic modulation was not prevented by exercise training. In conclusion, AAS produced cardiac autonomic dysfunction and ventricular repolarization disturbances in rats. Combining an exercise training protocol during the AAS treatment attenuated the ventricular repolarization abnormalities and did not prevent cardiac autonomic dysfunction.
Keywords: electrocardiography; exercise training; heart rate variability; nandrolone decanoate; spectral analysis